Effects of ultrasound irradiation on Au nanoparticles deposition on carbon-coated LiNi0.5Mn1.5O4 and its performance as a cathode material for Li ion batteries - Yasuyuki Tanaka; Hirokazu Okawa; Takahiro Kato; Katsuyasu Sugawara (Ultrasonics Sonochemistry, 2022)
LiNi0.5Mn1.5O4 (LMNO) has attracted considerable attention as a Li-ion battery cathode material, owing to its high discharge voltage of 4.7 V (vs. Li/Li+) and high energy density. However, the electronic conductivity of LMNO is low, resulting in a low discharge capacity at high current density. To overcome this limitation, we deposited Au nanoparticles (NPs), which have a high conductivity and chemical stability at high battery voltages, on carbon-coated LMNO (LMNO/C) using ultrasound irradiation. Consequently, Au NPs that are ∼16 nm in size were deposited on LMNO/C, and ultrasound irradiation was reported to disperse the NPs on LMNO/C more effectively than stirring. Furthermore, the deposition of Au NPs on LMNO/C using ultrasound irradiation improved its electronic conductivity, which is related to an increase in the discharge capacity due to the reduction of Ni4+ to Ni2+ in LMNO/C at a high current density.